Pengungkapan Corporate Social Responsibility Sebagai Bentuk Komunikasi Citra Perusahaan - Ni Putu Ari Aryawati; I Ketut Putu Suardana (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
The aim of this study to examine the influence of corporate social responsibility disclosure as a legitimation of firm image at go public firm. Based on legitimacy theory, there is a possible corporate social responsibility disclosure as a maintain corporate image to community. The sample of this research is manufacturing company which are listed in Indonesia Stock Exchange (IDX) in 2018 – 2020. The result of this research shows that more detail and higher disclosure corporate social responsibility, the higher of corporate image. This result provides legistimation theory for support the environmental firm.